The Effect of Sedentary Lifestyle on the Incidence of Obesity on Adolescents in SMUN 7 Banda Aceh - Yuliana Asnita; Evawany Yunita Aritonang; Zulhaida Lubis (Britain International for Academic Research (BIAR) Publisher, 2020)
The number of obesity populations worldwide has risen sharply in the last decade. Obesity does not only occur in adulthood but can also be experienced in childhood and adolescence. Many factors cause obesity, minimal physical activity is one of the factors causing obesity in adolescents. This type of research is an observational analytic study with a case-control design. The population of the study was all students of class X and XI at SMUN 7 Banda Aceh. The sample was divided into two groups: cases with students who had obesity nutritional status and a control group with students who had normal nutritional status. The sample size for the case were 50 students and cases of 100 students, the total sample were 150 students. Sampling was done by systematic random sampling technique. The research data were analyzed using univariate analysis and bivariate analysis. The results showed that variables related to obesity were watching TV (p = 0.021, OR = 2.48, CI = 1,208-5,126), using gadgets (p = 0,023, OR = 3,83, CI = 1,254 - 11,719), doing tasks with internet (p = 0,000 OR = 5,16 CI = 2,483-10,749) doing tasks without internet (p = 0.002 OR = 3.25 CI = 1,588-6,650) following less and recite (p = 0.003 OR = 3.143 CI = 1,511- 6,537) get together with friends (p = 0.002 OR = 3,273 CI = 1,611-6,697).